Quality of life in informal carers of individuals with multiple sclerosis - Topcu, Gogem (2016)
Caring for a relative or friend with Multiple Sclerosis (MS) may negatively impact the quality of life (QoL) of carers. However, in the existing literature, there are no adequate scales available to measure MS carers’ QoL due to the lack of satisfactory conceptualisation and operationalisation of QoL in MS caregiving. This has limited the ability to have a consistent body of evidence to guide further MS carer QoL research and practice. Therefore, this research aimed to systematically investigate the factors that enhance or compromise the lives of MS carers by utilising the theoretical construct of QoL. In so doing, the research sought to develop and validate an MS-specific QoL measure for informal carers (MSQoL-C). A sequential mixed-methods approach was utilised to explore QoL among MS carers and to inform the development of the MSQoL-C. First, a meta-synthesis of 17 qualitative studies on MS informal caregiving was conducted (Study 1) to improve the conceptual understanding of the experiences of MS carers. The synthesis resulted in 9 inter-linking themes: Changes and losses; MS and patient-related challenges; caregiving demands; burden of care; future concerns; external stressors; support; coping and motivating factors. This synthesis presented a model for MS caregiving and a preliminary list of operationalisations of QoL that needed further exploration. Second, in order to explore the QoL of MS carers and investigate the factors that enhance or compromise their QoL, a photovoice study (Study 2) was conducted with 12 MS carers. Study 2 established that MS carers often experience MS caregiving-related challenges, personal losses and changes, negative emotions, an urge to escape and a unique sense of anxiousness over the unpredictability of their MS carer role. However there were also some positive elements that emerged, such as the happy moments and the supporting role of loved ones, that helped ameliorate these negative events and enhance QoL. Study 3 was an online interview study conducted with six MS carers in order to triangulate the findings from Studies 1 and 2, and to derive a more comprehensive understanding of the QoL issues in MS caregiving. Interview data were analysed using Interpretative Phenomenological Analysis and findings yielded three super-ordinate themes: Difficulties of MS caregiving, Satisfaction/Dissatisfaction with life and Consequences of MS caregiving. Study 3 provided further support that QoL of MS carers is substantially compromised and that they experience a number of unique MS-specific obstacles within their caregiving role. Finally, the findings from these three studies informed the development of the MSQoL-C, and a pilot study (Study 4) was conducted to test its psychometric properties. The MSQoL-C was found to have good congruent validity, internal consistency and test-retest reliability. It is envisaged that the MSQoL-C will provide an understanding of the factors that impact upon MS carers’ QoL, and will be useful to implement and evaluate therapeutic interventions.